Rumah Rengganis: A Cross-Generational Community Literacy Platform - Dinda Dwi Destarini; Farida Nurfalah (Journal Research of Social Science, Economics, and Management, 2026)
The development of literacy culture in Indonesia shows improvement, but has not yet fully reached a high level nationwide. Amid the wave of digitalization, literacy is no longer understood merely as the ability to read and write, but rather as a social practice and a medium of communication. This study aims to analyze the role of the Rumah Rengganis Literacy Community in Cirebon City as a medium for social expression and reflection. The study employs a qualitative approach using in-depth interviews with five informants, observation, documentation, journals, and books. Data analysis utilizes symbolic interaction theory grounded in the concepts of mind, self, and society to understand the process of meaning-making through literacy interactions. The findings reveal that literacy at Rumah Rengganis is interpreted as a practice of social meaning-making that connects texts with the realities of life. This community functions as an egalitarian space for symbolic interaction, where works and discussions shape the construction of social reality. Furthermore, Rumah Rengganis serves as an alternative, informal public space that fosters critical dialogue and intergenerational participation. This study recommends strengthening policy support, cross-community collaboration, and the development of further research to expand the role of independent literacy communities in building social awareness and literacy-based public spaces at the local level.